Poverty and International Migration : A Multi-Site and Intergenerational Perspective - Eroğlu, Sebnem (Polity Press shorts research., 2022)
International migration is a life-changing process, but do the migrants and their families fare economically better than those who stayed behind? Drawing on the largest database available on labour migration to Europe, this book seeks to shed light upon this question through an exploration of poverty outcomes for three generations of settler migrants spanning multiple European destinations, as compared with their returnee and stayer counterparts living in Turkey. As well as documenting generational trends, it investigates the transmission of poverty onto the younger generations. With its unique multi-site and intergenerational perspective, the book provides a rare insight into the economic consequences of international migration for migrants and their descendants.